Daily field checking list by Walter Rosene, May 29, 1941 - Iowa Ornithologists' Union; Rosene, Walter, 1880-1941 (1941)
Daily field checking list of birds observed in Boone County by Walter Rosene and Robert Walker, May 29, 1941. Also notes their observation of a Ruddy Turnstone.